Positive Steady States of an Indefinite Equation with a Nonlinear Boundary Condition: Existence, Multiplicity, Stability and Asymptotic Profiles - Ramos-Quoirin, H (Springer New York LLC, 2016)
We investigate positive steady states of an indefinite superlinear reaction-diffusion equation arising from population dynamics, coupled with a nonlinear boundary condition. Both the equation and the boundary condition depend upon a positive parameter λ, which is inversely proportional to the diffusion rate. We establish several multiplicity results when the diffusion rate is large and analyze the asymptotic profiles and the stability properties of these steady states as the diffusion rate grows to infinity. In particular, our results show that in some cases bifurcation from zero and from infinity occur at λ= 0. Our approach combines variational and bifurcation techniques. © 2016, Springer-Verlag Berlin Heidelberg.